Analisis perhitungan dan pemotongan PPh pasal 22 atas pengadaan barang pada Kantor Perwakilan Pemda Kabupaten Kepulauan Talaud di Manado - Wae, Dominika; Sabijono, Harijanto; Lambey, Robert (Indonesia Accounting Journal, 2019)
The business sector of both individuals as well as legal entities has an obligation to deposit and report the tax payable. One example of the activities of a business entity that is required to deposit and report the tax payable is the business activities of procurement of goods and services. Procurement of goods and services for local government basically in terms to fulfill required of the goods and services expertise. The purpose of this study is to describe the calculating and reporting income tax especially for Article 22 on procurement of goods at the Regional Government Regional Representative Office of Talaud in Manado. This study uses method is quantitative descriptive method in period of 2016. The results show that the PPh Article 22 shall be imposed at rate of 1.5% and shall be paid by using document called SSP to the perception bank appointed by the Minister of Finance. This study finds that the calculation of income tax article 22 of Regional Government Regional Representative Office of Talaud in Manado is following the recent taxation regulation.